Extended global routing with RLC crosstalk constraints. - Jinjun Xiong (IEEE Transactions on VLSI systems)
In this paper, we study an extended global routing problem with RLC crosstalk constraints. Considering simultaneous shield insertion and net ordering, we propose a multiphase algorithm to synthesize a global routing solution with track assignment to satisfy the RLC crosstalk constraint at each sink. The key algorithm phase is global routing synthesis with shield reservation and minimization based on prerouting shield estimation. Experiments using large industrial benchmarks show that compared to the best alternative with postrouting shield insertion and net ordering, the proposed algorithm with shield reservation and minimization reduces the congestion by 18.4% with a smaller runtime. To the best of our knowledge, this is the first in-depth study on global routing synthesis with RLC crosstalk constraints.